Test of Flat Burr Mill Grinder On The commodity of Rice, White Sticky Rice and Black Sticky Rice - Endra Rahmadan; S Bahri Daulay; Sulastri Panggabean (Jurnal Rekayasa Pangan dan Pertanian, 2014)
Changing the form of rice, white sticky rice and black sticky rice into flour is one way to increase the sale value or economic value of the material, in which rice flour, white sticky rice flour and black sticky rice flour are widely used as a raw material in the manufacture of foodstuffs. This study was a test of flat burr mill grinder on the commodity of rice, white sticky rice and black sticky rice. The study was conducted with literature study, experiment, observation and testing of equipment and experiment using a non-factorial completely randomized design (CRD). Parameters measured were the effective capacity of the equipment, the percentage of lost material and moisture content. The results showed that the effective capacity on rice was 11.29 kg/hour, white sticky rice was 11.81 kg/hr and black sticky rice was 12.29 kg/hour. The percentage of material lost was 0.50% for rice, 0.72% for white sticky rice and 0.45% for black sticky rice. The water content of rice before milled was 14.4%, 14.4% white sticky rice and black sticky rice by 13.8%. The water content of rice after milling was 14.2%, 13.8% for white sticky rice, and black sticky rice was 13.3%. Keywords: flat burr mill, grinder, rice, white sticky rice, black sticky rice